The COVID-19 Handbook Navigating the Future of Healthcare. - Schneider, Jason (Relias LLC, 2020)
The COVID-19 Handbook: Navigating the Future of Healthcare provides factual, evidence-based information on the coronavirus disease 2019 (COVID-19) pandemic.